Factors of Success for Libraries on the Ballot - Valerie McNutt (The Political Librarian, 2023)
Is there a set of conditions that will largely pre-determine the results on Election Day? Are there any specific choices by management that can be made in the lead-up to a campaign to create favorable conditions?